O JĘZYKU SPECJALISTYCZNYM W KONTEKŚCIE KULTUROWYM NA PRZYKŁADZIE BŁĘDNEGO UŻYCIA JĘZYKA NIEMIECKIEGO W LIŚCIE MOTYWACYJNYM - Bawej, Izabela (Neofilolog, 2020)
This paper investigates a particular aspect of teaching languages for special purposes. The article focuses on the cultural component in the analysis of error in the collocation in Wort und Schrift that occurs in job applications written by students of Applied Linguistics. Learners of German as a foreign language for special purposes use the mother tongue and they coin words that do not exist in German. Errors of this type are a result of the cultural differences between languages and in-adequate intercultural competence.